Functional and Radiological Outcome of Gartland Type 2 and 3 Supracondylar Fracture Humerus in Children Treated by Percutaneous Pinning - Muhammad Nadeem Kashmiri, Asif Khan, Omer Khalid Farooq, Zubair Janan Orakzai, Sumaira Noureen, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The supracondylar humeral fractures were the most common fracture of the paediatric elbow with a high incidence between the ages 5 to 14 years. The aim of this study was that to compare the functional and radiological outcome between Gartland type II and III by percutaneous spinning surgery treating method in children. Study design: The study was cross sectional being conducted at the orthopedic department of Watim Medical College Rawat, Rawalpindi for the duration of six months, from June 2022 to December 2022. Methodology: The age range was >5 and <13 years. The children age, gender, affected area, post-operative loss of reduction and complications were recorder. The functional and radiological outcomes were follow up at least 7-8 weeks. Flynn’s criteria and Baumann angle were used to assess elbow movement after surgery. Results: A total number of patients was 110 operated for supracondylar humeral fracture which divide into 55 patients in each type of Gartland fractures. The maximum children 82%, p=0.01* were belong to age group 6-12 years which show significant. The left side 55%, p=0.009 was more injured as compared to right side. According to Flynn’s rating, Gartland 2 and 3 show significant improvement; p=0.001** of fractures after treatment. All patients had show satisfactory results in terms of loss of carrying angle, and elbow flexion. The data was analyzed by SPSS21. Conclusions: The percutaneous spinning show better clinical outcome of radiological and functional between two types of fracture Gartland 2 and 3 suprcondylar humeral fracture after treatment in children. Keywords: Humerus, Range of motion, injury, Fracture.